A highly stable microporous boron-doped diamond electrode etched by oxygen plasma for enhanced electrochemical ozone generation. Issue 6 (December 2021) - Liu, Fangmu; Deng, Zejun; Miao, Dongtian; Chen, Weipeng; Wang, Yijia; Zhou, Kechao; Ma, Li; Wei, Qiuping
Graphical Abstract: ga1 Abstract: The boron-doped diamond (BDD) electrode, having ultra-high oxygen evolution potential and anodic stability, is potentially considered the ideal candidate for the next-generation ozone generator despite the relatively low current efficiency. In this work, we first report using a microporous BDD electrode etched by oxygen plasma, denoted as p-BDD, to improve the performance of electrochemical ozone generation. Two parameters, including O2 plasma etching temperature and time, are experimentally optimized. We demonstrated that the electrochemically active surface area (ECSA) of the optimal p-BDD is 2.51 times that of the bare BDD, and this p-BDD shows about one-quarter lower charge transfer resistance than the latter. Under the same unit energy consumption, the p-BDD has 3.76 times the ozone generation capacity compared to the latter. The p-BDD shows excellent long-term stability, only having 4.2% of the decrease in the current density up to 40 h of consecutive water electrolysis under the steady-state period, and it also remains a 100% recovery rate in its capability of electrochemical performance after mild treatment by cycling at a diluted sulfuric acid solution for 200 s Highlights: A microporous BDD electrode etched by O2 plasma (p-BDD) is fabricated. We first report the use of p-BDD to carry out electrochemical ozone generation. p-BDD has 3.76 times the capacity of ozone generation compared to the bare BDD. p-BDD shows excellent stability with only 4.2% of current decrease within 40 h test. p-BDD remains a 100% recovery rate in electrochemical performance after mild treatment.